2022
DOI: 10.1371/journal.pone.0271565
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of pigeonpea (Cajanus cajan [L.] Millspaugh) landraces grown in Benin revealed by Genotyping-By-Sequencing

Abstract: Genetic diversity studies provide important details on target trait availability and its variability, for the success of breeding programs. In this study, GBS approach was used to reveal a new structuration of genetic diversity and population structure of pigeonpea in Benin. We used a total of 688 high-quality Single Nucleotide Polymorphism markers for a total of 44 pigeonpea genotypes. The distribution of SNP markers on the 11 chromosomes ranged from 14 on chromosome 5 to 133 on chromosome 2. The Polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Moghaddam et al [ 1 ] also reported high within-population variation in tepary bean, concurring with the present findings. Farmers and breeders may have selected tepary bean genotypes for certain agronomic traits, resulting in considerable genetic differentiation among populations [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moghaddam et al [ 1 ] also reported high within-population variation in tepary bean, concurring with the present findings. Farmers and breeders may have selected tepary bean genotypes for certain agronomic traits, resulting in considerable genetic differentiation among populations [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the lack of sufficient characterization of genetic resources and by ricochet the lack of genetic data constitute for any crop the main brake to any improvement program [7]. Genetic diversity studies by discovering and characterizing novel genes or alleles likely to be introgressed into elite germplasm seem to be the primary basis for successful plant breeding [8].…”
Section: Introductionmentioning
confidence: 99%